Corneal thickness in dry eyes in an Iraqi population - Ali NM (Dove Medical Press, 2017)
Noora Mauwafak Ali,1 Furkaan M Hamied,1 Qasim K Farhood2 1Department of Surgery, College of Medicine, Al-Qadisiya University, Diwaniyah, 2Department of Surgery, College of Medicine, University of Babylon, Hillah, Iraq Background: Dry eye disorder is a multifactorial disease of the tears and ocular surface that results in discomfort and visual disturbance. Corneal pachymetry becomes increasingly important in refractive surgery, for the accurate assessment of intraocular pressure, and in the preoperative assessment of other ocular surgeries. Purpose: To assess the effect of dry eye disorder on the central corneal thickness (CCT) by comparing with CCT of normal eyes of age-matched individuals. Patients and methods: The total number of eyes examined was 280 (140 dry eyes from 70 patients and 140 normal eyes from 70 individuals). Pentacam (Scheimpflug imaging system) was used for measuring the CCT of all eyes. Results: Patients with dry eye syndrome had significantly lower CCT compared to the control group (P<0.01). Its mean was 536.5 versus 561.3, respectively. Conclusion: CCT of dry eyes was significantly reduced when compared with age- and gender-matched population. This result can be attributed to chronic desiccation by the inflammatory mediators in dry eyes, leading to corneal thinning. Keywords: central corneal thickness, pentacam, dry eye syndrome